Quantitative Finance Stack Exchange is a question and answer site for finance professionals and academics. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In many textbooks and also in the original Merton's paper the solution of the SDE

$$ dS_t = S_t\,\mu\,dt+S_t\,\sigma\,dW_t+S_{t^-}\,d\left(\sum_{j=1}^{N_t}V_j-1\right) $$

is written as

$$ S_t = S_0\,\exp\left(\left(\mu-\frac{1}{2}\,\sigma^2\right)\,t+\sigma\,W_t\right)\,\prod_{j=0}^{N_t}V_j. $$

Can someone suggest me a textbook or a paper where the solution is explicitly derived? I am pretty confident that this is an application of the Ito lemma for semimartingale.

share|improve this question
up vote 10 down vote accepted

Let $$ dS_t = \mu S_t dt + \sigma S_t dW_t + S_{t^-} dJ_t $$ where $$ J_t = \sum_{j=1}^{N_t} (V_j - 1) $$ is a compound Poisson process, with $V_j$ i.i.d. jump sizes (positive random variables) whose statistical properties are not relevant for what needs to be proven and $N_t$ a standard Poisson process of intensity $\lambda$. The processes $W_t$, $N_t$ and the random jump sizes $V_j$ are all assumed to be independent of each other and defined over the same probability space.

Applying Itô's formula for semi-martingales with jumps to the function $f(t,S_t) = \ln(S_t)$ yields (see here) $$\ln(S_t) = \ln(S_0) + \left(\mu - \frac{\sigma^2}{2} \right)t + \sigma W_t + \int_0^t ( \ln(S_u) - \ln(S_{u^-}) )dN_u $$ From the SDE we then have that, at a jump time $u$ $$ S_u - S_{u^-} = S_{u^-} (V_j - 1) \iff S_u = S_{u^-} V_j $$ such that $$ \ln(S_u) - \ln(S_{u^-}) = \ln\left(\frac{S_u}{S_{u^-}}\right) = \ln(V_j) $$ and therefore $$ \ln(S_t) = \ln(S_0) + \left(\mu - \frac{\sigma^2}{2} \right)t + \sigma W_t + \sum_{j=1}^{N_t} \ln(V_j) $$ Finally, because $$\sum_{j=1}^{N_t} \ln(V_j) = \ln \left( \prod_{j=1}^{N_t} V_j \right) $$ we get \begin{align} S_t &= S_0 \exp \left( \left(\mu - \frac{\sigma^2}{2} \right) t + \sigma W_t \right) \prod_{j=1}^{N_t} V_j \\ &= F(0,t) \mathcal{E}(\sigma W_t) \prod_{j=1}^{N_t} V_j \end{align} with $\mathcal{E}(X_t) := \exp(X_t - 1/2 \langle X \rangle_t)$ denoting the stochastic exponential of a process $X_t$ (Doléans-Dade exponential).

More info on jump processes (and better mathematical treatment because what I wrote is not always rigorous) in this excellent document


Note that because \begin{align} E_0[S_t] &= F(0,t) E_0\left[\prod_{j=1}^{N_t} V_j\right] \\ & \ne F(0,t) \end{align} the above dynamics cannot be used for risk-neutral pricing purpose.

To obtain a proper risk-neutral framework, the compound Poisson process needs to get compensated by a drift term (so that the whole emerges as a martingale). The resulting SDE writes

$$ dS_t = (\mu - k) S_t dt + \sigma S_t dW_t + S_{t^-} dJ_t $$

where one can show that $$ k = \lambda (E(V_1) - 1) $$

and where the solution in that case reads $$ S_t = F(0,t) \mathcal{E}(\sigma W_t) e^{-kt} \prod_{j=1}^{N_t} V_j $$

share|improve this answer

Use Ito for jumps $$ dS_t = \frac{\partial S_t}{\partial t} dt + \frac{\partial S_t}{\partial W_t}dW_t + \frac{1}{2}\frac{\partial^2 S_t}{\partial W_t^2} dt + \frac{\partial S_t}{\partial N_t}d N_t $$

The first part is pretty straight forward

$$ \frac{\partial S_t}{\partial t} dt = S_t(\mu - \frac{1}{2}\sigma^2) $$ $$ \frac{\partial S_t}{\partial W_t}dW_t = S_t \sigma dW_t $$ $$ \frac{1}{2}\frac{\partial^2 S_t}{\partial W_t^2} dt = \frac{1}{2} S_t\sigma^2 dt. $$

Now we have to calculate the derivative according to the jump process $N_t$

Denote $ M_k = \prod_{j=1}^{k} V_j$ and write

$$ M_t = \prod_{j=1}^{N_t} V_j = \sum_{k=1}^\infty\{N_t = k \} \prod_{j=1}^{k} V_j = \sum_{k=1}^\infty\{N_t = k \} M_k. $$

Now if $N_t$ is currently $k$ and jumps during the timestep $t$ to $t+dt$ from $k$ to $k+1$ the process $M_t = M_k$ changes to $M_{t+dt} = M_{k+1}$ and the change is $$ M_{k+1} - M_k = M_k(V_{k+1} - 1). $$

Therefore, and since $N_t$ has no influence on $\exp((\mu + \sigma^2)t + \sigma W_t)$

$$ \frac{\partial S_t}{\partial N_t} = S_{t-}(V_t - 1)$$

Now note that $$(V_t - 1)dN_t = d\sum_{j=1}^{N_t} (V_j - 1)$$ and you are finished.

share|improve this answer
    
Could you clarify what you mean when you write $\partial^2 S_t / \partial S_t^2$ ? – Quantuple Mar 24 at 13:06
    
That was a typo. I meant $\partial^2S_t/\partial W^2_t$. – Phun Mar 24 at 13:49
    
OK thanks. I now understand what you did. It shows that $S_t$ as given by the OP indeed verifies the SDE. Yet, it doesn't explain how to find $S_t$ starting from the SDE. – Quantuple Mar 24 at 13:54

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.